Byzantine Elements of the Material Culture of the Thirteenth-Fourteenth Century Bosporos (On the Example of 2018 Excavation Trench) - Maiko, Vadim Vladislavovich (Antičnaâ drevnostʹ i srednie veka, 2021)
This paper is the first to address the problem of the presence of Byzantine imports in the material culture of Bosporos from the second half of the thirteenth and fourteenth centuries. So far the degree of “Byzantinization” of the coastal towns in the eastern Taurica, which were finally absorbed by the Golden Horde in the third quarter of the thirteenth century and remained in its structure to the mid-fifteenth century, is a topical issue in the mediaeval Crimean studies. Although the greatest part of the artefacts made in Byzantium, represented mostly by ceramic ware and discovered in the thirteenth-fourteenth century horizons and buildings of Sougdaia, has already been introduced into the scholarship, parallel finds from Bosporos never became the subject of analysis. The reason is the poor studying of the latter and almost complete absence of published materials. The materials of large-scale protective excavations conducted in Kerch in 2018 certainly deserve attention. The vast majority of these finds date from the seventh to twelfth centuries. However, the materials from the second half of the thirteenth and fourteenth centuries stand out to become the subject of this paper. Unfortunately, they are highly fragmented, but allowing the one to determine Byzantine imports and to compare their composition and quantity with similar products of Sougdaia.